A simple procedure in a complex patient: perioperative takotsubo cardiomyopathy. Issue 12 (17th December 2020) - Jothin, Arvind; Raj, John Prakash; Thiruvenkatarajan, Venkatesan
Abstract : Takotsubo cardiomyopathy (TTC) is a rare but life-threatening condition that is still not completely understood. Characterised by rapidly reversible ventricular dysfunction without any prior coronary artery disease, it can imitate a myocardial infarction and lead to death if not managed appropriately. This report examines a case of intraoperative cardiac arrest in a patient with no previous cardiac disease, and discusses the factors that may have precipitated this event, as well as the ways of distinguishing the cause of the arrest based on clinical course and investigations, eventually leading to a diagnosis of TTC.